Mehrzielselektierung bei der Bauvorbereitung - Zavadskas, Edmundas K. (Journal of Civil Engineering and Management, 1995)
Multi-purpose selectonovation in preparation of constructional work The article deals with the major problems of decision making in building construction. The schemes describing stages of decision making are presented. The main principles of decision making in building construction are discussed and the sequence of decision-making processes is generalized. An evaluation classification of multi-factorial alternatives is worked out. Five stages of multiple criteria selectonovations in building construction are characterized. The article also presents a mathematical model of multiple criteria solutions. Statybos gamybos daugiatikslė selektonovacija Santrauka. Straipsnyje analizuojamos pagrindinės sprendimų priėmimo statyboje problemos, pateikiamos schemos, charakterizuojančios sprendimų priėmimo etapus. Analizuojami pagrindiniai sprendimų priėmimo principai, formalizuota bendra sprendimų priėmimo eiga. Atlikta daugiafaktorinių alternatyuų įvertinimo klasifikacija. Aptariami daugiakriterijinės selektonovacijos penki etapai bei suformuluotas daugiakriterijinių sprendimų matematinis modelis. Article in German. First Published Online: 26 Jul 2012